SUSCEPTIBILITY OF SOME COWPEA VARIETIES TO THE SEED BEETLE, CALLOSOBRUCHUS MACULATUS (F.)(COLEOPTERA: CHRYSOMELIDAE) - Musa, Abdulrassak Kannike (Journal of Agricultural Sciences (Belgrade), 2017)
ABSTRACT The study evaluated seven cowpea Vigna unguiculata L. Walp. varieties: IT89K-568-18, IFE-98-12, IT81P-994, IT89K-288, IT96-660, `Milk` and `Drum` for susceptibility to the seed beetle, Callosobruchus maculatus (F.) (Coleoptera: Chrysomelidae). Seed samples (100 g) of each variety were infested with 5 pairs of the seed beetle (1-2 days old) with three replications at 30±20C and relative humidity of 69-72%. The parameters evaluated include: number of damaged and undamaged seeds, percentage seed weight loss, mean number of emerged adults, median development period and susceptibility index. The percentage seed weight loss in IT96-660 was significantly (p